Reference and pro rail scenarios for European corridors to 2050 - Claus Doll; Jonathan Hugh Köhler (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2018)
This paper feeds into Stream 2 of the LowCarb-RFC study. It seeks to construct a Business-as-Usual scenario and a more ambitious Pro Rail scenario for freight transport along two major European rail freight corridors: RFC 1 (Rhine-Alpine) from the Dutch seaports to northern Italy and RFC 8 (North Sea-Baltic) from the Belgium seaports to Poland. The main focus of the scenarios is on the railways, but for a complete picture road haulage and inland navigation are considered as well.
urn:nbn:de:0011-n-5065869; Additional information: Working Paper 5 of the study LowCarb-RFC - European Rail Freight Corridors going Carbon Neutral.
Keywords: 330